Rituximab for the treatment of type B insulin resistance syndrome: a case report and review of the literature. Issue 12 (15th November 2017) - Iseri, K.; Iyoda, M.; Shikida, Y.; Inokuchi, T.; Morikawa, T.; Hara, N.; Hirano, T.; Shibata, T.
Abstract: Background: Type B insulin resistance syndrome is a rare disease characterized by refractory transient hyperglycaemia and severe insulin resistance associated with circulating anti‐insulin receptor antibodies. A standardized treatment regimen for type B insulin resistance syndrome has yet to be established. Case report: We report the case of a 64‐year‐old man undergoing haemodialysis for antineutrophil cytoplasmic antibody‐associated vasculitis and diabetic nephropathy, who developed rapid onset of hyperglycaemia (glycated albumin 52.1%). Type B insulin resistance syndrome was diagnosed, on the basis of positivity for anti‐insulin receptor antibodies and the man's autoimmune history of antineutrophil cytoplasmic antibody‐associated vasculitis and idiopathic thrombocytopenic purpura. Although severe hyperglycaemia persisted in spite of corticosteroids and high‐dose insulin therapy, rituximab treatment resulted in remarkable improvement of the man's severe insulin resistance and disappearance of anti‐insulin receptor antibodies without any adverse effects. Conclusions: According to a literature review of 11 cases in addition to the present case, rituximab appears to be a safe and effective strategy for the treatment of corticosteroid‐resistant type B insulin resistance syndrome. What's new?: We describe a case of type B insulin resistance syndrome and antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis and idiopathic thrombocytopenic purpura in a man undergoing haemodialysis. Rituximab treatment eliminated anti‐insulin receptor antibodies and improved the characteristics of the anti‐insulin antibody. Good glycaemic control was achieved after the administration of rituximab.